Dietary Pattern of School-Going Children during COVID-19 Pandemic - Singh, Brij Pal; Sharma, Mahak (International Journal of Child Health and Nutrition, 2022)
Background: School age is the foundation of human life. A healthy and balanced diet plays a major role in the proper growth development of the body as well as the mind. Only a balanced diet can provide all the macro and micronutrients. Covid 19 has impacted each and every human being in some or another manner. School-going children had to cope with new encounters involving online teaching-learning methodology and social distancing. As a result, these children have undergone mental and psychological trauma. This led them to follow faulty dietary habits, which would have long time impact on their health. Aim and Objectives: In the present survey, an attempt has been made to compile a report on the dietary intake of school-going children in the Roopnagar district of Punjab, India. Methodology: For the purpose sample of 100 students (7 to 12 years) was selected from four development blocks of district Roopnagar, and the cluster sampling method was adopted for data collection. A detailed pretested questionnaire on the dietary habits of children was used. Results: 59% of children were vegetarian, 32% were non-vegetarian, and 9% were eggetarian. Study findings showed that children preferred some of the items such as wheat, rice, sugar, rajma, black gram, green gram, potato, tomato, onion, apple, banana, and grapes over other food items in the same food group. Conclusion: Results showed that children do not consume a variety of food items, and some selected food items only resulting low dietary diversity and food variety.